Effect of COD/ NO3−-N ratio on nitrite accumulation and microbial behavior in glucose-driven partial denitrification system - Zeng, Zhijie; Wang, Yiying; Zhu, Wenxuan; Xie, Tian; Li, Lingling (Heliyon, 2023)
COD/NO3−-N ratio was considered to be one of the key factors achieving effective nitrite accumulation during partial denitrification. In two parallel reactors incubated with glucose as carbon source at COD/NO3−-N of 3 and 5, respectively, the microbial community structure shift and the nitrite accumulation performance during long-term operation were investigated. The maximum nitrite accumulation ratios at COD/NO3−-N of 3 and 5 were 17.9% and 47.04%, respectively. Thauera was the dominant genus in both reactors on day 220 with the relative abundance of 18.67% and 64.01%, respectively. Batch experiments with different electron acceptors suggested that the distinction in nitrite accumulation at COD/NO3−-N of 3 and 5 might be caused by the differences in the abundance of Thauera. [Display omitted] •The bacterial structure in PD was significantly related to the C/N ratio.•NAR was much higher at C/N of 5 than that at C/N of 3.•The distinction in NAR at C/N of 3 and 5 might be related with Thauera abundance.